P84 NKp46+ TRAIL- CD49b+ group 1 innate lymphoid cells mediate hepatitis in an interferon-γ dependent manner. (19th June 2022) - Lo, Jonathan; Cozzetto, Domenico; Stolarczyk, Emilie; Lavender, Paul; Kudo, Hiromi; Goldin, Robert; Lord, Graham; Powell, Nick
Abstract : Introduction: Hepatitis is major cause of morbidity and mortality globally. It is increasingly recognised that innate immune mechanisms are important in driving pathology. A heterogeneous family of innate lymphoid cells (ILCs) are now appreciated to be important effector cells in various pathological settings. Furthermore, the activation of the immune system via CD40 interactions to generate an inflammatory response in the liver has not previously been investigated. This study defines hepatic ILC populations and evaluates their potential role in causing liver disease. Methods: Rag -/- mice were treated with an agonistic anti-CD40 drug and culled after one week. Clinical data was collected in the form of weight loss, changes in organ mass and histology. The livers of these mice were then analysed using bulk RNA-seq, flow cytometry and ELISAs to measure the immune mediators of the disease. Mice were also treated with an anti-IFNγ or anti-IL22 antibody prior and during the treatment of anti-CD40, as well as various cell depletion antibodies, in order to determine their effects on this liver pathology. Results: We found that innate lymphocytes in the liver are dominated by NKp46 + expressing cells upon administering agonistic anti-CD40 monoclonal antibodies to Rag2 -/- mice. Unexpectedly indirect activation of hepatic ILCs (through CD40 stimulation) in Rag1 -/- (C57/BL6) and Rag2 -/- (Balb/C) mice resulted in marked hepatomegaly, focal areas of liver necrosis and elevation of serum transaminases (>10 fold) consistent with acute hepatocellular injury. These were also found to be independent of the microbiota. Focal areas of liver necrosis were surrounded by NKp46 + cells. Flow cytometric analysis of the liver demonstrated accumulation of NKp46 + CD90 + TRAIL - CD49b + ILCs, which produced high levels of interferon-γ (IFNγ). qPCR and RNA sequencing confirmed increased transcripts encoding Ifng and Tnfa, as well as upregulation of the interferon signalling pathways and Ifng and Tnfa being key upstream regulators involved in the liver during induction of pathology. Notably, mice additionally deficient for the Il2rg gene, which encodes the common γ–chain cytokine receptor, were resistant to disease. Depletion of NKp46 + cells, blockade of IFNγ or IL-22 attenuated disease showing a role for these in mediating the disease. Conclusion: Here, we have described a new innate immune-mediated model of acute, severe hepatitis following activation of innate immunity through stimulation of the anti-CD40 pathway. This model is driven by IFNγ production from NK cells and can be reversed upon blockade of IFNγ or IL-22.